Synergistic effect of interleukin-6 and endoplasmic reticulum stress inducers on the high level of ABCG2 expression in plasma cells - Nakamichi, Naoto; Morii, Eiichi; Ikeda, Jun-Ichiro; Qiu, Ying; Mamat, Suhana; Tian, Tian; Fukuhara, Shirou; Aozasa, Katsuyuki (Nature Publishing Group, 2009)
ABCG2 is a transporter preferentially expressed in a primitive subpopulation of cells and recently reported as a surviving factor for trophoblasts. To date, manner of ABCG2 expression in lymphoid tissues is not known. Immunohistochemically, strong ABCG2 expression was found in a small proportion of plasma cells mainly located in the interfollicular space of lymphoid tissues. The number of ABCG2-high plasma cells increased in interleukin-6- (IL-6) rich lesions, such as Castleman's disease of plasma cell type. Plasma cells are subjected to endoplasmic reticulum (ER) stress when excess proteins are synthesized, and IL-6 stimulates protein synthesis. Therefore, the effect of IL-6 and ER stress on ABCG2 expression in plasma cells was examined. The expression level of ABCG2 increased by treatment with either IL-6 or ER stress inducers, and further increased with both. The promoter analysis revealed that the effect of IL-6 and ER stress inducers was mediated through the site overlapping XBP-1 and HIF-1 binding sequences. Knocked-down of ABCG2 by siRNA or ABCG2 inhibitor reduced plasma cell viability under ER stress. These suggest that ABCG2 is a surviving factor for plasma cells. To our knowledge, this is the first study reporting the effect of ER stress on ABCG2 expression.